Neurologic Wilsons Disease and its Management - An Update (Bangladesh Journal of Child Health, 2014)
Wilsons disease is an inborn error of copper metabolism caused by mutations in the ATP7B gene. The disease has an autosomal recessive mode of inheritance and is characterized by excessive copper deposition, predominantly in the liver and brain. Clinical manifestations of neurologic Wilsons disease include variable combinations of dysarthria, dystonia, tremor, and choreoathetosis. Among neurodegenerative disorders. WD is preventable and treatable if they are diagnosed treated early. Untreated case of Wilsons disease progresses to severe neurologic disability and death, while those adequately treated have normal life spans. The traditional treatment for WD is based on copper chelation with agents such as D-penicillamine, but use of this drug has been questioned because of reported side effects. The use of agents such as Zinec, trientine and ammonium tetrathiomolybdate has been advocated, although results of long-term trials are awaited. This review focuses on the neurologic features of Wilsons disease and treatment options. DOI: http://dx.doi.org/10.3329/bjch.v37i3.18620 Bangladesh J Child Health 2013; Vol.37(3): 158-169